Cdc42 Effector Protein 3 Interacts With Cdc42 in Regulating Xenopus Somite Segmentation - Kho, Mary; Shi, Hongyu; Nie, Shuyi (Frontiers in Physiology, 2019)
Somitogenesis is a critical process during vertebrate development that establishes the segmented body plan and gives rise to the vertebra, skeletal muscles, and dermis. While segmentation clock and wave front mechanisms have been elucidated to control the size and time of somite formation, regulation of the segmentation process that physically separates somites is not understood in detail. Here, we identified a cytoskeletal player, Cdc42 effector protein 3 (Cdc42ep3, CEP3) that is required for somite segmentation in Xenopus embryos. CEP3 is specifically expressed in somite tissue during somite segmentation. Loss-of-function experiments showed that CEP3 is not required for the specification of paraxial mesoderm, nor the differentiation of muscle cells, but is required for the segmentation process. Live imaging analysis further revealed that CEP3 is required for cell shape changes and alignment during somitogenesis. When CEP3 was knocked down, somitic cells did not elongate efficiently along the mediolateral axis and failed to undertake the 90-degree rotation. As as result, cells remained in a continuous sheet without an apparent segmentation cleft. CEP3 likely interacts with Cdc42 during this process, and both increased and decreased Cdc42 activity led to defective somite segmentation. Segmentation defects caused by Cdc42 knockdown can be partially rescued by the overexpression of CEP3. Conversely, loss of CEP3 resulted in the maintenance of high levels of Cdc42 activity at the cell membrane, which is normally reduced during and after somite segmentation. These results suggest that there is feedback regulation between Cdc42 and CEP3 during somite segmentation and the activity of Cdc42 needs to be fine-tuned to control the coordinated cell shape changes and movement required for somite segmentation.